RBM15-mediated metabolic reprogramming boosts immune response in colorectal cancer - Wang, Chen; Chen, Mengyan; Chen, Panyu; Han, Jinlu; Hu, Hong; Chen, Jiong; Wu, Qiong; Zhao, De; Wang, Tongshuai; Zhou, Jingyi; Li, Qi; Zhou, Runkai; et al. (Frontiers in Immunology, 2025)
IntroductionImmune checkpoint blockade (ICB) therapy has shown promise in treating advanced colorectal cancer, particularly in patients with microsatellite instability-high (MSI-H) tumors. However, only a subset of these patients responds favorably, highlighting the need for strategies to improve immunotherapy efficacy.MethodsTo identify potential regulators of immunotherapy response, we conducted a comprehensive analysis of colorectal cancer datasets from The Cancer Genome Atlas (TCGA). We performed multi-omics analyses and functional assays in both human and murine colorectal cancer cell lines. Additionally, we evaluated tumor growth and immune cell infiltration using syngeneic mouse models.ResultsOur analysis revealed that RNA binding motif protein 15 (RBM15) is highly expressed in colorectal cancer and correlates with poor patient prognosis. Functional studies demonstrated that RBM15 loss led to increased expression of fumarate hydratase (FH). This led to decreased levels of fumarate, a metabolite known to suppress anti-tumor immune responses. In vivo, RBM15 depletion significantly delayed tumor progression and enhanced CD8⁺ T cell infiltration and activation in the tumor microenvironment.DiscussionThese findings identify RBM15 as a negative regulator of anti-tumor immunity in colorectal cancer. Targeting RBM15 may represent a novel strategy to boost immune responsiveness and improve outcomes for patients undergoing immunotherapy.